2015
DOI: 10.1007/s00167-015-3842-y
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the PCL during the tibial cut in total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Several studies have drawn attention to how much of the PCL is actually preserved in a CR TKA, with several of them showing that most of the PCL insertion may be disrupted during the tibial cut, calling into question how much of the PCL is actually preserved. 24,[30][31][32][33][34] Liabaud et al used magnetic resonance imaging (MRI) to show that the majority (79.8%) of patients had more than 50% of the PCL destabilized following a standard transverse tibial cut. 30 Shannon et al also using MRI demonstrated that up to one-third of patients had complete removal of the PCL insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have drawn attention to how much of the PCL is actually preserved in a CR TKA, with several of them showing that most of the PCL insertion may be disrupted during the tibial cut, calling into question how much of the PCL is actually preserved. 24,[30][31][32][33][34] Liabaud et al used magnetic resonance imaging (MRI) to show that the majority (79.8%) of patients had more than 50% of the PCL destabilized following a standard transverse tibial cut. 30 Shannon et al also using MRI demonstrated that up to one-third of patients had complete removal of the PCL insertion.…”
Section: Discussionmentioning
confidence: 99%
“…32 Cinotti et al demonstrated that the PCL insertion could be spared in the majority of patients if the tibial cut is 4 mm or less with a slope of 3 to 5 degrees. 33 With the possibility that most CR TKAs have the majority of the PCL insertion damaged during the tibial cut, the actual role and the necessity of the PCL in a CR TKA are called into question. In the Cochrane Review, Jacobs et al showed that PCL resection without substituting the PCL with a PS TKA design showed no difference compared with PCL retention group (p ¼ 0.31).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been described to balance the ligaments and releasing the PCL completely may result worse outcomes [18,19,20,21]. Some studies have drawn attention that most PCL insertions may be destroyed during tibia cutting, and which raises questions about how much PCL actually saves in a CR TKA [18,[22][23][24][25][26]. Eric Kim et al [10] studied the incidence and risk factors of PCL avulsion during CR TKA, they found the incidence is 1.7% and female gender was the only risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive release of the ligaments may result in worse outcomes [17][18][19][20]. In many cases, the PCL insertion may be damaged during the tibial cut, which raises a question about how much the PCL is actually preserved [17,[21][22][23][24][25]. Some surgeons argued that a posterior-stabilized TKA with a spine-cam mechanism is an alternative when the PCL is sacri ced.…”
Section: Discussionmentioning
confidence: 99%